2021
DOI: 10.1007/s11240-021-02112-4
|View full text |Cite
|
Sign up to set email alerts
|

Using a combination of chitosan, methyl jasmonate, and cyclodextrin as an effective elicitation strategy for prenylated stilbene compound production in Arachis hypogaea L. hairy root culture and their impact on genomic DNA

Abstract: Peanut (Arachis hypogaea L.) hairy roots are a potential tool for stilbene compound production. This study focuses on the most e cient elicitation strategy for inducing stilbene compound production, especially for the prenylated forms of trans-arachidin-1 and trans-arachidin-3. To the best of our knowledge, this is the rst report of simultaneous treatment involving chitosan (CHT), methyl jasmonate (MeJA), and cyclodextrin (CD); CHT+MeJA+CD in peanut hairy roots to induce substantial amounts of trans-arachidin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Pre-soaking of chickpea seeds with 30 mM H 2 O 2 for 24 hr prior to germination revealed that after 72 hr, there were higher levels of total phenolic compounds and antioxidant activity compared to the control group (León-López et al, 2020). The current results were consistent another report on elicitor treatment in peanut hairy root culture that demonstrated an increase in ABTS antioxidant activity following CHT, MeJA, CD or CHT+MeJA+CD treatments (Chayjarung et al, 2021). However, the antioxidant activity detected in the treated peanut sprouts was much lower than in the hairy root culture system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Pre-soaking of chickpea seeds with 30 mM H 2 O 2 for 24 hr prior to germination revealed that after 72 hr, there were higher levels of total phenolic compounds and antioxidant activity compared to the control group (León-López et al, 2020). The current results were consistent another report on elicitor treatment in peanut hairy root culture that demonstrated an increase in ABTS antioxidant activity following CHT, MeJA, CD or CHT+MeJA+CD treatments (Chayjarung et al, 2021). However, the antioxidant activity detected in the treated peanut sprouts was much lower than in the hairy root culture system.…”
Section: Discussionsupporting
confidence: 92%
“…Batch-fed V. vinifera cell suspension culture treated with 50 mg/L of chitosan increased mono-glucosylated stilbene production (Ferri et al, 2011). Another study on hairy root peanut culture demonstrated the promising outcome of enhancing trans-resveratrol, trans-arachidin-1 and trans-arachidin-3 with high antioxidant activity using elicitor treatments of CHT, MeJA, CD and simultaneously CHT + MeJA + CD (Chayjarung et al, 2021). The use of an external elicitor treatment could be a promising strategy for increasing the production of phytochemicals and bioactive compounds in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, a natural biopolymer found in shrimp or insect shells (Malerba and Cerana 2015 ) is a low-cost, safe, and nontoxic compound (Chayjarung et al 2021 ) that has the potential to induce the production of secondary metabolites in plants (Jiao et al 2018 ). Chitosan is known to potentially trigger plant defense responses, forming a semipermeable film around plant tissue (Ghauth et al 1994 ; Pérez-Alonso et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, treatment of hairy roots from peanut cv. Kalasin 2 with chitosan, MeJA, and CD induced a large amount of arachidin-1 and arachidin-3 [19]. However, a study comparing the biological properties of stilbenoid-rich extracts from hairy roots of different peanut cultivars have not been done thoroughly.…”
Section: Introductionmentioning
confidence: 99%